Determinant of employee engagement at the workplace: A review on herzberg’s two factor theory - Nurul Hafizah, Ahmad Zubir (2022)
This research examines the relationship between motivation factors and hygiene factors with employee engagement among support staff in KPJ Ampang Puteri Specialist Hospital. This study aims to identify whether there is any relationship between motivation factors and hygiene factors with employee engagement among the chosen population. In this study, a quantitative approach was conducted, in which primary data were collected through an online questionnaire. The collected data through the questionnaire recorded 212 respondents from the KPJ Ampang Puteri Specialist Hospital support staff. The healthcare organisation was chosen to be the main focus of this study in which the sample consists of the organisation’s support staff. For the questionnaire, the researcher used a seven-Likert scale with the intention to measure the degree of motivation factors, hygiene factors, and employee engagement. This study used descriptive statistics, reliability tests, Pearson's correlation analysis, and Multiple Regression analysis to analyse the relationship. Based on the result obtained through this analysis, for the independent variable, motivation factors and hygiene factors have a significant relationship with employee engagement. Moreover, this study has also presented a great number of past studies proving the relationship with all variables along with the effectiveness of Herzberg’s two- factors and employee engagement. The success of this research includes a positive impact as well.